A rhoptry protein, localizing in the bulb region of rhoptries, could induce protective immunity against Eimeria tenella infection - Shi, Tuan-yuan; Zhou, Si-han; Kong, Ya-ru; Fu, Yuan; Liu, Yan; Yan, Wen-chao; Zhou, Yong-xue; Zhang, Liang; Hao, Li-li; Sun, Hong-chao (Frontiers in Immunology, 2023)
Rhoptry organelle proteins (ROPs) secreted by apicomplexan parasites play important roles during parasites invasion and survival in host cells, and are potential vaccine candidates against apicomplexan diseases. Eimeria tenella (E. tenella) is one of the most noteworthy apicomplexan species, which causes hemorrhagic pathologies. Although dozens of putative E. tenella ROP sequences are annotated, most ROP proteins are not well studied. RT-qPCR analysis of the E. tenella ROP21 gene (EtROP21) revealed that its mRNA levels were higher in merozoites and sporozoites than in sporulated and unsporulated oocysts. Then, recombinant EtROP21 protein (rEtROP21) was expressed in Escherichia coli, purified with nickel column and identified with western blot. Finally, we investigated the localization of EtROP21 in sporozoites and its protective efficacy against E. tenella infection in chickens. An EtROP21 gene fragment with an open reading frame (ORF) of 981 bp was obtained from the Beijing strain of E. tenella. The rEtROP21 has a molecular weight of approximately 50 kDa and was recognized by rEtROP21-immunized mouse serum. Two specific protein bands, about 43 KDa and 95 KDa in size, were detected in the whole sporozoite proteins using the rEtROP21-immunized chicken serum. Immunofluorescence and immunoelectron analyses showed that the EtROP21 protein predominantly localizes in the bulb region of rhoptries distributed at anterior, posterior, and perinuclear regions of E. tenella sporozoites. Immunization and challenge experiments revealed that immunizing chickens with rEtROP21 significantly increased their average body weight gain while decreasing mean lesion score and oocyst output (P <0.05). When compared with the challenged control group, the rEtROP21-immunized group was associated with a significantly higher relative weight gain (90.2%) and a greater reduction in oocyst output (67%) (P <0.05). The anticoccidial index of the rEtROP21-immunized group was 163.2. Chicken serum ELISA revealed that the levels of the specific anti-rEtROP21 antibody, IFN-γ, and IL-4 were significantly higher in the rEtROP21-immunized group than in the challenged control group (P <0.05). These results indicate that rEtROP21 can induce a high level of specific immune response and it is a potential candidate for the development of vaccines against E. tenella infection in chickens.